Design, synthesis, and biological evaluation of a novel series of peripheral-selective noradrenaline reuptake inhibitors—Part 2. Issue 14 (15th July 2016) - Yukawa, Tomoya; Fujimori, Ikuo; Kamei, Taku; Nakada, Yoshihisa; Sakauchi, Nobuki; Yamada, Masami; Ohba, Yusuke; Ueno, Hiroyuki; Takiguchi, Maiko; Kuno, Masako; Kamo, Izumi; Nakagawa, Hideyuki; et al.
Graphical abstract: Abstract: Peripherally selective inhibition of noradrenaline reuptake is a novel mechanism for the treatment of stress urinary incontinence to overcome adverse effects associated with central action. Herein, we describe our medicinal chemistry approach to discover peripheral-selective noradrenaline reuptake inhibitors to avert the risk of P-gp-mediated DDI at the blood–brain barrier. We observed that steric shielding of the hydrogen-bond acceptors and donors (HBA and HBD) of compound1 reduced the multidrug resistance protein 1 (MDR1) efflux ratio; however, the resulting compound6, a methoxyacetamide derivative, was mainly metabolized by CYP2D6 and CYP2C19 in the in vitro phenotyping study, implying the risk of PK variability based on the genetic polymorphism of the CYPs. Replacement of the hydrogen atom with a deuterium atom in a strategic, metabolically hot spot led to compound13, which was mainly metabolized by CYP3A4. To our knowledge, this study represents the first report of the effect of deuterium replacement for a major metabolic enzyme. The compound13, N -{[(6 S, 7 R )-7-(4-chloro-3-fluorophenyl)-1, 4-oxazepan-6-yl]methyl}-2-[(2 H 3 )methyloxy]acetamide hydrochloride, which exhibited peripheral NET selective inhibition at tested doses in rats, increased urethral resistance in a dose-dependent manner.